Theorizing and Studying Response to Norm Conflict - Anchalee Rüland (Norms in Conflict, 2022)
Since the constructivist turn in the 1980s, IRT has dealt extensively with norms and agency in normative environments. Central elements of this literature have analyzed the impact of norms on state behavior,¹ their diffusion and localization,² as well as their evolution, contestation, and change.³ Among scholars working on Southeast Asia, a norm-centered social-constructivist view of intraregional relations has in fact been so successful that constructivism has established itself as the mainstream approach to the study of ASEAN since the early 2000s.⁴ Yet the issue of norm conflict has remained theoretically and empirically understudied both in IR theorizing generally and in